2018
DOI: 10.1111/epi.14068
|View full text |Cite
|
Sign up to set email alerts
|

The primary prevention of epilepsy: A report of the Prevention Task Force of the International League Against Epilepsy

Abstract: Among the causes of epilepsy are several that are currently preventable. In this review, we summarize the public health burden of epilepsy arising from such causes and suggest priorities for primary epilepsy prevention. We conducted a systematic review of published epidemiologic studies of epilepsy of 4 preventable etiologic categories-perinatal insults, traumatic brain injury (TBI), central nervous system (CNS) infection, and stroke. Applying consistent criteria, we assessed the quality of each study and extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 66 publications
(110 reference statements)
0
59
0
7
Order By: Relevance
“…Traumatic brain injury (TBI) is an important cause of death and hospital admissions worldwide. There were approximately 2.8 million TBI-related emergency department visits, hospitalizations, and deaths in the United States in 2013[1, 2], and more than 1.4 million hospital admission and deaths related to TBI in Europe in 2012. [3] The consequences of TBI as measured by age-standardized disability-adjusted life-years lost are significant and the Global Burden of Disease Study 2016 identified TBI as a leading cause of disability worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is an important cause of death and hospital admissions worldwide. There were approximately 2.8 million TBI-related emergency department visits, hospitalizations, and deaths in the United States in 2013[1, 2], and more than 1.4 million hospital admission and deaths related to TBI in Europe in 2012. [3] The consequences of TBI as measured by age-standardized disability-adjusted life-years lost are significant and the Global Burden of Disease Study 2016 identified TBI as a leading cause of disability worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, our study suggests that this highly enriched study population may require a much shorter follow‐up period and the enrollment process may be faster because these EEG findings are not restricted to a single etiology. The incidence of epilepsy after stroke and hemorrhage ranges from 10%–14% . In comparison, 40.7% of the cases and only one (3.7%) control with such etiologies developed epilepsy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy is a brain disorder denoted by the predisposition to generate seizures accompanied by emotional and cognitive dysfunction [1]. Currently, there are estimated to be 50-70 million people worldwide suffering from epilepsy but only about 70% of them respond well to existing antiepileptic drugs [2,3]. Furthermore, epileptic patients suffer deteriorating quality of life as they face limitations on their physical activities and daily life as well as being subjected to prejudice due to their seizures [4].…”
Section: Introductionmentioning
confidence: 99%